2003
DOI: 10.1177/0013161x03251140
|View full text |Cite
|
Sign up to set email alerts
|

The Three Faces of Power: The U.S. Supreme Court’s Legitimization of School Authority’s Parental, Police, and Pedagogic Roles

Abstract: In its decisions New Jersey v. T.L.O. (1985) and Vernonia v. Acton (1995), the U.S. Supreme Court legitimated the actions and policies of school authorities. In doing so, it also defined and legitimated the following three roles of school authorities: agent-of-state, custodial, and tutelary. Hence, the role of school authorities and the nature of their relationship with students has become a vacillating one. This article explores the trichotomous roles cited in these U.S. Supreme Court decisions. It also exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Research has shown there are several theoretical frameworks and correlating disciplinary models that examine teacher influence on classroom management and discipline; however, there are far fewer identifying administrator disciplinary philosophy and management (Baker, 2005; Beyda Lorie & Lee, 2007; Celikten, 2001; Sokal, Smith, & Mowat, 2003; Zuckerman, 2007). This lag in administrative understanding is substantial as school authorities are often charged with several roles regarding students, including agent of state, custodial, and tutelary (Ehrensal, 2003; Marks & Nance, 2007). To fulfill these roles, school administrators must establish a safe educational environment and make final decisions regarding student behavior (Celikten, 2001; Glanz, 2004).…”
Section: Established Disciplinary Theoretical Frameworkmentioning
confidence: 99%
“…Research has shown there are several theoretical frameworks and correlating disciplinary models that examine teacher influence on classroom management and discipline; however, there are far fewer identifying administrator disciplinary philosophy and management (Baker, 2005; Beyda Lorie & Lee, 2007; Celikten, 2001; Sokal, Smith, & Mowat, 2003; Zuckerman, 2007). This lag in administrative understanding is substantial as school authorities are often charged with several roles regarding students, including agent of state, custodial, and tutelary (Ehrensal, 2003; Marks & Nance, 2007). To fulfill these roles, school administrators must establish a safe educational environment and make final decisions regarding student behavior (Celikten, 2001; Glanz, 2004).…”
Section: Established Disciplinary Theoretical Frameworkmentioning
confidence: 99%